RETHINKING THE BLACK SEA: BETWEEN THE TRANS-ATLANTIC AND THE EURASIAN PROJECTS - Cioculescu, Åžerban Filip (Scientia Militaria - South African Journal of Military Studies, 2013)
The Black Sea region as a buffer between great powers and cordon sanitaire was and still is important in European history. After the 18th century, the Russian empire began a gradual but unstoppable move towards the conquest of the region, leading to a setback for Turkish influence. The Crimean War enabled Western powers to contain Russian expansion for some decades. For small and medium-sized countries like Romania, it is difficult to erase historic experiences from their collective memory. During the Cold War, the Black Sea was a virtual “Soviet lake” from a military point of view. The West controlled only the straits “owned” by Turkey following the Montreux Convention. After the implosion of the USSR, this strategic area was neglected by the Western powers and viewed by the Russian Federation as a traditional sphere of influence. Since 1991, Ukraine holds about 30% of the northern shore of the Black Sea, Georgia controls roughly 12% of the maritime littoral (including the separatist territories) while Russia owns about 13% of the Black Sea shores. Turkey and Ukraine hold the biggest share of the Black Sea shore. Generally speaking, during the two last decades, there have been two competing visions about the future: the Euro-Atlantic one, which insists on opening and internationalising the sea, and the Eurasian vision, which wants the Black Sea to remain closed and impenetrable to foreign interferences. This article deals with these issues. doi: 10.5787/41-1-1051